Rekonstruksi Makna Qiwāmah dalam Qs An-Nisā’ [4]:34: Pendekatan Sosio-Historis - Muh. Nasruddin A; Abubakar, Achmad; Sohrah, Sohrah (IAIN KENDARI, 2026)
This article examines the meaning of qiwāmah in QS An-Nisā’ [4]:34 through linguistic, Qur’anic semantic and socio-historical approaches. The study employs a qualitative library research method by integrating Fazlur Rahman’s double movement theory, Abdullah Saeed’s contextualist approach and Toshihiko Izutsu’s Qur’anic semantics. The analysis focuses on the linguistic structure of the verse, the semantic field of qiwāmah and the socio-historical context of early Arab society that shaped gender relations in classical tafsir. The findings indicate that qiwāmah does not represent the ontological superiority of men over women, but rather a functional and contextual social responsibility. The phrases bimā faḍḍala and bimā anfaqū demonstrate that qiwāmah is closely related to economic responsibility and family management rather than permanent domination. This study proposes an integrative interpretive model that combines linguistic analysis, Qur’anic semantics and socio-historical approaches in understanding gender-related Qur’anic verses contextually while remaining grounded in the Islamic exegetical tradition.